Host tissue identification for cryptic hymenopteran parasitoids associated with Sirex noctilio. (7th October 2015) - Foelker, Christopher J.; Standley, Christopher R.; Fierke, Melissa K.; Parry, Dylan; Whipps, Christopher M.
Abstract: Establishing host–parasitoid relationships is challenging for cryptic insects feeding deep in the xylem tissue of trees. Sirex noctilio is a xylophagous feeder and recent invader of North America that co‐occurs in pines ( Pinus ) with a native siricid ( Sirex nigricornis ) and a suite of shared hymenopteran parasitoids. This insect has a long history as a destructive pest in Southern Hemisphere pine plantations. To establish explicit trophic linkages between native hymenopteran parasitoids and two species of woodwasp ( Sirex ) in North America, a polymerase chain reaction assay was developed to amplify mitochondrial DNA that was restriction digested with the aim of identifying species. The assay was used to identify species of Sirex from cadavers and gut contents from different parasitoid stages with the aim of establishing host–parasitoid relationships. The host woodwasp species was identified successfully from parasitoid gut contents collected from larvae, pupae and adults. Across all parasitoid life stages, woodwasp host was identified in 52.9% of ibaliid parasitoids and 78.5% of rhyssine parasitoids. Host was successfully identified from 88.1% of associated siricid cadavers. These results demonstrate the utility of molecular techniques to verify host–parasitoid associations that previously had only been inferred. Development of molecular tools is a rapid and crucial tool for establishing trophic linkages and is particularly useful in situations involving non‐native species with cryptic lifestyles.